Palladium‐Catalyzed Allylic Alkylation of 2‐Aryl‐1, 3‐Dithianes, an Umpolung Synthesis of β, γ‐Unsaturated Ketones. Issue 3 (29th November 2018) - Trongsiriwat, Nisalak; Li, Minyan; Pascual‐Escudero, Ana; Yucel, Baris; Walsh, Patrick J.
Abstract: Palladium‐catalyzed allylic alkylation of 2‐aryl‐1, 3‐dithianes at room temperature is described. A variety of cyclic and acyclic electrophiles successfully coupled with in‐situ generated 2‐sodio‐1, 3‐dithiane nucleophiles to afford the allylated products in good to excellent yields (25 examples). Deprotection of these products leads to valuable β, γ‐unsaturated ketones. Direct synthesis of such β, γ‐unsaturated ketones via a one‐pot allylation‐oxidation protocol is also presented. Investigation into the stereochemistry of the allylation reaction revealed that the 2‐sodio‐1, 3‐dithiane nucleophile behaves as a "soft" nucleophile, which underwent external attack on the π‐allyl palladium complex to provide retention of stereochemistry (double inversion pathway). Additionally, the utility of this method was demonstrated through a sequential one‐pot allylation‐Heck cyclization to produce asterogynin derivatives, which are important bioactive compounds in medicinal chemistry. Abstract :